Anhedonia requires MC4 receptor-mediated synaptic adaptations in nucleus accumbens - Lim, Byung Kook (2012)
Chronic stress is a strong diathesis for depression in humans and is used to generate animal models of depression. It commonly leads to several major symptoms of depression including dysregulated feeding behavior, anhedonia, and behavioral despair. Although hypotheses defining the neural pathophysiology of depression have been proposed, the critical synaptic adaptations in key brain circuits that mediate stress-induced depressive symptoms remain poorly understood. Here we show that chronic stress decreases the strength of excitatory synapses on D1 dopamine receptor-expressing nucleus accumbens medium spiny neurons due to activation of melanocortin 4 receptors (MC4Rs). Stress-elicited increases in behavioral measurements of anhedonia, but not increases in measurements of behavioral despair, are prevented by blocking these MC4R-mediated synaptic changes in vivo. These results establish that stress-elicited anhedonia requires a neuropeptide-triggered, cell type-specific synaptic adaptation in the nucleus accumbens and that distinct circuit adaptations mediate other major symptoms of stress-elicited depression.